A Rare Venous Port Complication: Supraventriculer Tachycardia - Tamer Yoldaş; Selmin Karademir; Mehmet Onur Çandır (Güncel Pediatri, 2016)
Implantable central venous port catheters are widely used in the management of children with cancer undergoing long term chemotherapy. These catheters can manifest a number of complications such as arrhythmia. Central venous port catheter was placed on a ten years old boy for chemotherapy. Before insertion of port catheter his physical examination, laboratory parameters, electrocardiography and echocardiography were normal. The patient felt palpitations shortly after the insertion of the port catheter. At that time the heart rate was 200 beats/minute but immediately normal sinus rhythm was restored. A chest roentgenogram revealed that the distal fragment of the port catheter was inside the right atrium. The port catheter was pulled back somewhat and then tachycardia attacks stopped. To our knowledge there are a few reports of supraventricular tachycardia (SVT) in children associated with central venous port catheter. Here we aimed to present a pediatric case with SVT after placement of central venous port catheter and his management.